Effect of Mediating Variable Job Satisfaction in Relationship of Organizational Commitment and Quality of Work Life of Workforce of Select IT Companies at Hyderabad - Joiceswarnalatha , Dr.R. (International Journal of Psychosocial Rehabilitation, 2020)
In present globalization era organization invest of human intellectuals for withstanding the heavy competition. The human resources often move from one organization to the other. This may be because of lack of commitment, contentment and quality of work life. The author primed to find the influence of organization commitment on quality of work life with mediation of employment satisfaction levels. The author chose IT professionals of Hyderabad as respondents. The facts were pooled by using questionnaire. The tools used for analysis were ANOVA, Regression and Process Macro. The outcome of the study showed that there was moderate association of organization commitment on quality of work life and job satisfaction was observed as partial mediator amid of organization commitment and quality of work life.